2015
DOI: 10.1002/adsc.201500608
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Alkene Cleavage Catalysed by Manganese‐Dependent Cupin TM1459 from Thermotoga maritima

Abstract: An ovel biocatalytic oxidative alkene cleavagea ctivity was identifiedi np rotein TM1459 from Thermotoga maritima,aso far uncharacterised metalloprotein with ac upinf old, which preferentially binds manganese (over iron and zinc). Va rious styrene derivatives were converted with high chemoselectivity to the corresponding carbonylc ompounds by the manganese-containing protein,u sing organic hydroperoxide and molecular oxygen as oxidant. 4-Chloroacetophenone could be obtainedi n4 0% conversion from 4-chloro-a-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…Site-saturation libraries of active site amino acids (Arg39, Phe41, Ile49, Trp56, Ile60, Phe94, Phe104, Cys106, and Ile108) were generated using primers with NNK codons. The plasmid pET26b(+)-TM1459 ( Hajnal et al, 2015 ) was used as template. For subsequent double and triple mutants, site-directed mutagenesis was performed using plasmids with TM1459 carrying one or two of the desired mutations as templates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Site-saturation libraries of active site amino acids (Arg39, Phe41, Ile49, Trp56, Ile60, Phe94, Phe104, Cys106, and Ile108) were generated using primers with NNK codons. The plasmid pET26b(+)-TM1459 ( Hajnal et al, 2015 ) was used as template. For subsequent double and triple mutants, site-directed mutagenesis was performed using plasmids with TM1459 carrying one or two of the desired mutations as templates.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction conditions for the bioconversion reactions were derived from Hajnal et al (2015) . The reactions were performed in a biphasic reaction system in 2 mL microreaction tubes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different proteins of different enzyme classes, which are heme, non-heme iron, or non-iron metal dependent and have different protein structures as well as different reaction mechanism are known to catalyze alkene cleavage reactions [3]. Specifically, an isoeugnol and trans-anethole oxygenase from Pseudomonas putida and two manganese dependent enzymes from Thermotoga maritima (manganese-dependent Cupin TM1459) and Trametes hirsuta (Mn 3+ -dependent proteinase A homologue) oxidatively cleaved the benzylic double bond of different aryl alkenes, such as isoeugenol and trans-anethole to form the respective aldehydes [6][7][8][9]. In addition, alkene cleavage activity towards aryl alkenes was also detected for several peroxidases.…”
Section: Introductionmentioning
confidence: 99%
“…[28] TM1459 is derived from hyperthermophile, whose scaffold is very thermally stable, and has a molecular mass of only 12 977 Da (residues 1-114) with a metal-binding site consisting of a 4-His metal binding motif (Figure 1 A); however, its function is unknown. [29,30] Herein, we have demonstrated that the small cupin variants of TM1459 ( Figure 1 B) can be effectively used to create efficient and robust biocatalysts for the stereoselective Michael addition reaction of nitroalkanes to a,b-unsaturated ketone, 2-azachalcone 1, achieving excellent diastereo-and enantioselectivity as well as high TON.…”
Section: Inmodernorganicsynthesisasymmetricreactionshavebeenmentioning
confidence: 98%